2020
DOI: 10.1002/lio2.418
|View full text |Cite
|
Sign up to set email alerts
|

Do high‐frequency air‐bone gaps persist after ossiculoplasty?

Abstract: Objectives Conventional reporting of postoperative hearing outcomes utilizes a pure‐tone averaged air‐bone gap (ABG) that is biased toward low frequencies. Consequently, a high‐frequency ABG after otologic surgery may go unnoticed. In this study, we evaluate changes in low‐ and high‐frequency ABG following ossiculoplasty. Study design Retrospective review. Subjects and setting Consecutive series of patients who underwent ossiculoplasty at a single tertiary care center. Patients with pre‐ and postoperative audi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…A statistically significant improvement in air conduction by 15.14 dB was found after undergoing incudostapedial reconstruction using conchal cartilage (p< 0.001). In agreement with our results, Polanik et al, [9] conducted a retrospective study to evaluate changes in low and high frequency ABG following ossiculoplasty. Reconstruction materials included: cartilage (N = 4), hydroxyapatite cement (N = 5), and partial or total ossicular replacement prostheses (N = 20 and N = 8, respectively).…”
Section: Discussionsupporting
confidence: 92%
“…A statistically significant improvement in air conduction by 15.14 dB was found after undergoing incudostapedial reconstruction using conchal cartilage (p< 0.001). In agreement with our results, Polanik et al, [9] conducted a retrospective study to evaluate changes in low and high frequency ABG following ossiculoplasty. Reconstruction materials included: cartilage (N = 4), hydroxyapatite cement (N = 5), and partial or total ossicular replacement prostheses (N = 20 and N = 8, respectively).…”
Section: Discussionsupporting
confidence: 92%
“…Our secondary analysis of the results from over 700 patients published by Pauli 2019 shows a more complete closure of the ABG at low frequencies than high frequencies with similar magnitudes to our data set. Our prior work on high‐frequency conductive hearing following middle ear surgery 9 , 10 suggests that across middle ear surgical procedures, post‐operative high frequency ABGs persist and may be under‐reported using current PTA 4 standards. 8 …”
Section: Discussionmentioning
confidence: 99%
“…A 2018 review by Cheng et al, demonstrated the short and long‐term durability of hearing improvements following stapedotomy using PTA data from several published series 6 . However, the traditional pure‐tone average (PTA 4 ) recommended by the American Academy of Otolaryngology‐Head and Neck Surgery (AAO‐HNS), 7,8 may not sufficiently communicate changes in high‐frequency (HF) conductive hearing 9,10 . HF bone conduction thresholds following stapes surgery have not been robustly studied and reported outcomes are variable 5,11‐13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation